Experimental investigation on a packaged unit of membrane dehumidification-based ventilation system - Hye-Jin , Cho; Seong-Yong, Cheon; Su-Young , Jo; Soo-Jin, Lee; Gyu-Bae, Lee; Jae-Weon, Jeong (CLIMA 2022 conference, 2022)
This study purposed to experimentally investigate the seasonal operating performance of the packaged unit of a hollow membrane-based ventilation system. The packaged unit of the proposed ventilation system was fabricated, and the experiments was conducted based on the test standards for the energy recovery ventilator addressed from air-conditioning, heating and refrigeration institute (AHRI). In addition, for achieving the optimal heat and moisture recovery from the ventilation system under various operating conditions, the seasonal operation modes were suggested for the packaged unit of the proposed ventilation system. The measured data showed that the proposed ventilation unit can provide the ventilation air ait nearly neutral air temperature and humidity ratio in each operation mode. In addition, the average sensible effectiveness, the average latent effectiveness, and the average enthalpy effectiveness of the proposed ventilation system are 70.7%, 75.9%, and 75.6% in mode 1; 44.4%, 74.7%, 80.2% in mode 2; 77.6%, 70.4%, 85.6% in mode 3, which exhibited the higher heat and moisture recovery performance compared to the commercial energy recovery ventilator. In conclusions, the measured data demonstrates that the proposed ventilation system has a great application potential for building ventilation unit in terms of energy recovery performance.